Efficient Transient Expression of Recombinant Proteins in Plants by the Novel pEff Vector Based on the Genome of Potato Virus X - Mardanova, Eugenia S.; Blokhina, Elena A.; Tsybalova, Liudmila M.; Peyret, Hadrien; Lomonossoff, George P.; Ravin, Nikolai V. (Frontiers in Plant Science, 2017)
Agroinfiltration of plant leaves with binary vectors carrying a gene of interest within a plant viral vector is a rapid and efficient method for protein production in plants. Previously, we constructed a self-replicating vector, pA7248AMV, based on the genetic elements of potato virus X (PVX), and have shown that this vector can be used for the expression of recombinant proteins in N. benthamiana. However, this vector is almost 18 kb long and therefore not convenient for genetic manipulation. Furthermore, for efficient expression of the target protein it should be co-agroinfiltrated with an additional binary vector expressing a suppressor of post-transcriptional gene silencing. Here, we improved this expression system by creating the novel pEff vector. Its backbone is about 5 kb shorter than the original vector and it contains an expression cassette for the silencing suppressor, P24, from grapevine leafroll-associated virus-2 alongside PVX genetic elements, thus eliminating the need of co-agroinfiltration. The pEff vector provides GFP expression levels of up to 30% of total soluble protein. The novel vector was used for expression of the influenza vaccine candidate, M2eHBc, consisting of an extracellular domain of influenza virus M2 protein (M2e) fused to hepatitis B core antigen (HBcAg). Using the pEff system, M2eHBc was expressed to 5-10% of total soluble protein, several times higher than with original pA7248AMV vector. Plant-produced M2eHBc formed virus-like particles in vivo, as required for its use as a vaccine. The new self-replicating pEff vector could be used for fast and efficient production of various recombinant proteins in plants.